Transforming coastal and marine management: Deliberative democracy and integrated management in New South Wales, Australia. (May 2022) - Brooks, Kate; Barclay, Kate; Grafton, R. Quentin; Gollan, Natalie
Abstract: The integrated management (IM) of coastal and marine environments is an enduring problem, particularly in multi-sectoral and jurisdictional systems, with coastal management of New South Wales (NSW), Australia being no exception. Historically, NSW coastal and marine management was dominated by ecological and economic approaches, implemented in parallel through multiple government agencies with overlapping jurisdictions. A review in 2012 of NSW marine park management recommended addressing the unintended consequences of this management approach, and the Marine Estate Management Act (2014), was established to integrate management of the whole of the NSW coast. This paper discusses the role that a deliberative democratic approach has played in the approach to IM undertaken by the NSW Marine Estate Management Authority (MEMA). The NSW MEMA case study provides a robust reflection of the challenges identified by the literature in implementing effective integrated management, being the alignment of values, visions and methods of assessment, across multiple resources, ecosystems, stakeholders and administrative jurisdictions. Deliberative democratic approaches were used in reviewing the MEMA case to analyse its ability to address some of the challenges and realise benefits of IM. However, despite benefits being identified, a key finding is that achieving integration across multiple agencies with varied disciplinary approaches and organisational cultures, takes a significant amount of time. Even after several years, challenges remain in embedding cultural shifts and resource commitment at all levels to ensure the ongoing successful implementation of IM. Highlights: Integrated management of marine and coastal resources is necessary in the increasingly complex environment. The application of IM principles requires particular governance definitions and attributes. Governance legitimacy is improved through the use of deliberative democratic approaches. The NSW Marine Estate Management strategy is an example of the use of deliberative democracy to improve the outcomes in developing and implementing integrated management for a coastal zone.